The analysis of the relationship between organizational values and commitment with regard to the knowledge management of Kermanshah’s tax department staff (Revista Lusófona de Educação, 2018)
The present research has been carried out under the title of “The analysis of the relationship between organizational values and commitment with regard to the knowledge management of Kermanshah’s Tax Department staff”. The study is descriptive from the viewpoint of its aim and method of data collection.The Statistical population of this study consists of chief administrative officers, middle-ranked officers and operating officers, a total number of whom reaches 396 individuals.195 individuals were chosen as statistical samples. The means of data collection is three types of questionnaire concerning organizational values, knowledge management, and organizational commitment. The results of data analysis prove that there is a meaningful correspondence between organizational values and knowledge management but not a meaningful relationship between organizational commitment and knowledge management. Likewise, there is a correlation between the variable that predicts organizational values and the variable of knowledge management, while there is no meaningful relationship between the variable of organizational commitment and that of knowledge management.Keywords: organizational values; organizational commitment; knowledge management.